Método de evaluación aplicado a talleres grupales de estudio de casos en la clase de administración de empresas - Iturralde Solórzano, Rafael Alberto (2014)
Modern methods of teaching and learning require an active participation of both the student and teacher. The application of active methods of teaching such as workshops and case studies are being increasingly used as tools in the classroom that help to fulfill the learning objectives. By observation and personal experiences of the authors, there has been a deficiency in the final part of the implementation of these methods regarding how to assess the knowledge acquired by the student. In this article its propose evaluation active methods, which have been implemented and subjected to a study throughout the first semester of 2014 in students of career Commercial Engineering of the Faculty of Administrative Sciences. Were noted two important effects, the first, a psychological commitment from all members of the group of students who develop the workshop or case as to learn to be evaluated at that time showed higher levels of care in activity were noted developed and secondly evidenced contribute to the formation of nonverbal communication in each one of them being actively evaluated during the development of the workshop. This article contribute to the improvement of these assets just giving methods that stage of evaluation, a greater role for students to develop workshops and classes cases.